(untitled) (ModaPalavra e-periódico, 2015)
This article, by reference to Brazil, aims to explore some meanings related to the twentieth century and adornments whether jewelry, costume jewelry and body ornaments. It was determined as a starting point the technological transformations generated by political and economic changes. The industrial modernization in the 1950s broughtcultural renewal which allowed new habits and customs that bore fruit in the forefront strands of contemporary Brazilian context. Adequate and bolder use of raw materials and the relationship between cost and benefit proved viable and boosted the world economy. Through field research and literature review, it was found that jewelry, bijouterie and corporal ornament had their boundaries approximated in the contemporary scope. The intersection of different approaches to analysis of some points in the design scope led the study.